AB0244 Development of an adjusted multi-biomarker disease activity (MBDA) score for rheumatoid arthritis (RA) that accounts for age, sex and adiposity, with subsequent evaluation of ability to predict risk for radiographic damage. (12th June 2018) - Curtis, J.R.; Flake, D.D.; Weinblatt, M.; Shadick, N.A.; Østergaard, M.; Hetland, M.L.; Heegaard Brahe, C.; Hwang, Y.G.; Furst, D.E.; Strand, V.; Etzel, C.J.; Pappas, D.; et al.
Abstract : Background: The MBDA score, based on 12 serum proteins, is a validated tool for assessing disease activity in RA patients. MBDA biomarkers may be influenced by age, sex and adiposity. Objectives: To develop and validate an adjusted MBDA score that accounted for these three factors, using BMI or serum leptin as proxies for adiposity. Methods: The MBDA score as a continuous variable was adjusted to account for age, sex and a proxy for adiposity (serum leptin) using data from 325, 781 RA patients for whom MBDA tests had been ordered as part of routine care. Leptin values came from the MBDA test. As an alternative to using leptin to adjust for adiposity, a cohort of 1411 patients from 5 studies/registries (BRASS, Corrona-CERTAIN, InFoRM, OPERA, RACER) was used to adjust for BMI, which was not available in the larger cohort, adding this BMI adjustment to that for age/sex from the larger cohort. Both types of adjusted MBDA score use the low, moderate, and high disease activity cutpoints of the original MBDA score. The two adjusted MBDA scores and other variables were evaluated for the prediction of radiographic progression (RP) in the 2 cohorts with available data (OPERA, BRASS) using univariate and multivariate linear regression analyses. Rate of RP was assessed as the change in modified total Sharp score (ΔmTSS) per year after MBDA testing. Results: The MBDA score increased with age, BMI and leptin concentration. In univariate analysis of the combined OPERA and BRASS cohorts (n=555), the significant variables predicting ΔmTSS were leptin-adjusted MBDA score, seropositivity for RF or anti-CCP, BMI-adjusted MBDA score, MBDA score, BMI, CRP, baseline mTSS, disease duration, DAS28-CRP, SDAI, CDAI and DAS28* (table 1). The leptin- and BMI-adjusted MBDA scores were the first and third most significant univariate predictors of ΔmTSS. To compare them directly, DAS28-CRP, MBDA score, BMI-adjusted MBDA score and leptin-adjusted MBDA score were combined in pairs in regression analyses of ΔmTSS; the BMI-adjusted (p=0.0027) and leptin-adjusted MBDA score were significant (p=0.00063) after adjusting for DAS28-CRP (p=0.87 and 0.74, respectively) and the leptin-adjusted MBDA score was significant (p=0.024 and 0.020, respectively) after adjusting for either the MBDA (p=0.32) or BMI-adjusted MBDA scores (p=0.094). Conclusions: We developed two adjusted MBDA scores that combine molecular and biometric variables to account for age, sex, and adiposity. The leptin-adjusted MBDA score, significantly outperformed DAS28-CRP and the original MBDA score in predicting radiographic progression in RA patients. These results suggest that the leptin-adjusted MBDA score may offer improved clinical utility for the personalised management of patients with RA. Disclosure of Interest: J. Curtis Grant/research support from: Crescendo Bioscience Inc., Consultant for: Crescendo Bioscience Inc., D. Flake II Shareholder of: Myriad Genetics, Inc., Employee of: Myriad Genetics, Inc., M. Weinblatt Grant/research support from: Amgen, Bristol-Myers Squibb, Crescendo Bioscience Inc., UCB, and Genzyme, Consultant for: Amgen, Bristol-Myers Squibb, Crescendo Bioscience Inc., UCP, and Genzyme, N. Shadick Grant/research support from: Bristol-Myers Squibb, Consultant for: Mallinckrodt, Amgen, Bristol-Myers Squibb, UCB, DxTerity, Sanofi, Crescendo Bioscience Inc., Janssen, and Merck, M. Østergaard Grant/research support from: Abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli-Lilly, Centocor, GSK, Hospira, Janssen, Merck, Novartis, Orion, Pfizer, Regeneron, Roche, Takeda, and UCB, Consultant for: AbbVie, BMS, Celgene, Crescendo Bioscience Inc., Janssen, and Merck, M. Hetland Consultant for: AbbVie, Biogen, BMS, CelltrionRoche, Crescendo Bioscience Inc., Eli Lilly, MSD, Pfizer, and UCB, Speakers bureau: Orion, C. Heegaard Brahe: None declared, Y. Hwang Consultant for: Pfizer Inc., D. Furst: None declared, V. Strand Grant/research support from: Abbvie, Amgen, AstraZeneca, BMS, Boehringer Ingelheim, Celgene, Celltrion, CORRONA, Crescendo Bioscience Inc., EMDSerono, Genentech/Roche, GSK, Janssen, Lilly, Merck, Novartis, Pfizer, Protagen, Regeneron, Samsung, Sandoz, Sanofi, and UCB, C. Etzel Shareholder of: CORRONA, LLC, Grant/research support from: Merck, Employee of: CORRONA, LLC, D. Pappas Shareholder of: CORRONA, LLC, Employee of: CORRONA, LLC, Paid instructor for: Novartis Pharmaceutical, X. Wang Shareholder of: Myriad Genetics, Inc., Employee of: Crescendo Bioscience Inc., C. Hwang Shareholder of: Myriad Genetics, Inc., Employee of: Crescendo Bioscience Inc., E. Sasso Shareholder of: Myriad Genetics, Inc., Employee of: Crescendo Bioscience Inc., A. Gutin Shareholder of: Myriad Genetics, Inc., Employee of: Myriad Genetics, Inc., E. Hitraya Shareholder of: Myriad Genetics, Inc., Employee of: Crescendo Bioscience Inc., J. Lanchbury Shareholder of: Myriad Genetics, Inc., Employee of: Myriad Genetics, Inc.